Positive electrode additive, positive electrode sheet and lithium-ion battery

By using LixAyC2O4 as the positive electrode additive for lithium-ion batteries, the tight adsorption effect of high-price state A is used to reduce the deliquency potential of Li, which solves the problem of lithium-ion consumption during the first charge and discharge of lithium-ion batteries, and improves the capacity and stability of the battery.

CN116417612BActive Publication Date: 2025-03-07BYD CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202111681175.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-30
Publication Date
2025-03-07
Estimated Expiration
2041-12-30

AI Technical Summary

Technical Problem

When the existing lithium-ion batteries are charged and discharged for the first time, lithium ions are consumed due to the formation of the SEI film, which reduces the charge and discharge efficiency. The commonly used lithium-enhancing material Li2C2O4 has a high deliquency potential, which limits its application.

Method used

LixAyC2O4 is used as the positive electrode additive for lithium-ion batteries, where the compound valence of A is ≥+2, 1

Benefits of technology

The release of active lithium at low potential is achieved for lithium replenishment, reducing the irreversible damage to the material structure at high voltage, and improving the capacity, stability and cycling performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116417612B_ABST
    Figure CN116417612B_ABST
Patent Text Reader

Abstract

The present invention provides a positive electrode additive for a lithium ion battery, wherein the positive electrode additive for a lithium ion battery is Li x A y C2O4, the valence of A is ≥ +2. The present invention also provides a lithium ion battery positive electrode sheet comprising the lithium ion battery positive electrode additive and a lithium ion battery comprising the positive electrode sheet. x A y Due to the introduction of doping atom A in the C2O4 structure, the close adsorption of A and anions weakens the interaction between Li and anions, making it easier for Li to be released during the charging process. It has a low delithiation potential and can be decomposed under short-term low voltage to complete the lithium replenishment of the negative electrode, avoiding the irreversible structural changes of the positive electrode active material under continuous high charging voltage conditions, thereby improving the stability and cycle performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of lithium ion batteries, and in particular relates to a positive electrode additive, a positive electrode plate and a lithium ion battery. Background Art

[0002] When a lithium-ion battery is charged and discharged for the first time, the solid-liquid interface between the electrode and the electrolyte will react to form a "passivation film", namely the SEI film, on the surface of the electrode material. The formation of the SEI film will consume some lithium ions, increase the irreversible capacity of the first charge and discharge of the lithium-ion battery, and reduce the charge and discharge efficiency. Therefore, it is necessary to supplement lithium to the electrode material to offset the lithium ion consumption caused by the formation of the SEI film and increase the capacity and energy density of the battery.

[0003] In the document "Sophie Solchenbach et al. Lithium Oxalate as Capacity and Cycle-Life Enhancer in LNMO / Graphite and LNMO / SiG Full Cells. Journal of The Electrochemical Society 165(3): A512-A524", it is reported that Li2C2O4 material decomposes and releases lithium at around 4.7V. The Li+ produced when Li2C2O4 decomposes can migrate to the negative electrode to replenish the active lithium consumed by the formation of the negative electrode SEI film. Li2C2O4 material can be used as a lithium supplement material. However, the document report shows that the potential (lithiation potential) at which Li2C2O4 decomposes and releases lithium ions is as high as 4.7V, which is only applicable to high-voltage lithium-ion battery systems, such as LiNi 0.5 Mn 1.5 O2 (working voltage 4.7-4.8V), while for most positive electrode materials, the delithiation potential value is much higher than its charging cut-off voltage, especially for ternary materials. The higher the charging voltage, the greater the irreversible change in its structure, which seriously affects its structural stability and cycle performance. The delithiation potential of Li2C2O4 limits its application as a lithium supplement material. Summary of the invention

[0004] The object of the present invention is to provide a lithium ion battery positive electrode additive with a lower delithiation potential, a positive electrode plate containing the additive material and a lithium ion battery.

[0005] The first aspect of the present invention provides a positive electrode additive for a lithium ion battery. The positive electrode additive for a lithium ion battery is Li x A y C2O4, the valence of A is ≥+2, 1<x<2.

[0006] The lithium ion battery positive electrode additive Li x A y In C2O4, the cation Li is +1, and the valence state of A is b≥2. The high valence state makes A and anions have a close adsorption effect. The close adsorption has two effects: first, it weakens the adsorption effect between Li and anions, making it easier to escape, making the additive material Li x A y C2O4 can decompose and release active lithium at a lower voltage (i.e., it has a lower lithium removal potential); secondly, it makes it difficult for A itself to be removed from Li x A y The release of C2O4 prevents the release of A ions to the negative electrode, thereby avoiding the occurrence of side reactions.

[0007] The lithium ion battery positive electrode additive Li x A y C2O4 has a low delithiation potential, which can reduce the delithiation potential to below 4.6V, so that active lithium can be released at low potential to replenish the consumption of the negative electrode SEI film. The low delithiation potential avoids irreversible damage to the material structure under high voltage, thereby improving the battery's capacity, stability and other electrochemical properties.

[0008] According to the principle of electrical neutrality, when A is an ion, the valence state of A b0 and x, y satisfy x + b0 * y = 2; when A includes more than two ions, Li x A y C2O4 can be specifically written as Li x A 1 y1 A 2 y2 ……A n yn C2O4, of which A 1 , A 2 , A n y The valence state is b1, b2...b n , satisfying x+b1*y1+b2*y2+……+b n *y n =2.

[0009] In some implementations of the present invention, the value range of x is 1.5≤x<2, preferably 1.9≤x<2.

[0010] In some embodiments of the present invention, A is selected from at least one of divalent cations, trivalent cations and tetravalent cations, preferably Mg 2+ , Ca 2+ , Fe 2+ 、Al 3+ , Fe 3+Cr 3+ 、Ti 4+ , Si 4+ At least one of Ge.

[0011] The above-mentioned “A is selected from at least one of divalent cations, trivalent cations and tetravalent cations” means that: A is a divalent cation, a trivalent cation or a tetravalent cation; or, A is a combination of divalent cations and trivalent cations, a combination of divalent cations and tetravalent cations, a combination of trivalent cations and tetravalent cations, or a combination of divalent cations, trivalent cations and tetravalent cations.

[0012] In some embodiments of the present invention, the above-mentioned Li x A y The average particle size of C2O4 is 50nm~10μm, preferably 100nm~1μm.

[0013] In some embodiments of the present invention, the above-mentioned Li x A y The delithiation potential of C2O4 is not higher than 4.6V; preferably, the above Li x A y The delithiation potential of C2O4 is 4.1V~4.6V.

[0014] The second aspect of the present invention provides a lithium ion battery positive electrode plate, comprising a positive electrode active material and the lithium ion battery positive electrode additive provided by the first aspect of the present invention.

[0015] In some embodiments of the present invention, the above-mentioned lithium ion battery positive electrode plate includes a positive electrode current collector and a positive electrode material layer disposed on the positive electrode current collector; the positive electrode material layer satisfies the following conditions (1) or (2):

[0016] (1) The positive electrode material layer comprises the above-mentioned lithium ion battery positive electrode additive and positive electrode active material mixed together;

[0017] (2) The positive electrode material layer includes a positive electrode active material layer and a positive electrode additive material layer provided on the positive electrode active material layer, the positive electrode active material layer includes a positive electrode active material, and the positive electrode additive material layer includes the lithium ion battery positive electrode additive.

[0018] Specifically, the "positive electrode material layer", "positive electrode active material layer" and "positive electrode additive material layer" may contain, in addition to the lithium-ion battery positive electrode additives and / or positive electrode active materials mentioned above, materials required for forming pole pieces, such as conductive agents and binders, etc. The conductive agents and binders may be selected from the conductive agents and binders commonly used in the art, which will not be described in detail here.

[0019] The positive electrode active material is selected from at least one of LiFePO4, LiMn2O4 and nickel-cobalt-manganese ternary material (NCM). In the lithium-ion battery positive electrode plate, the mass ratio r of the lithium-ion battery positive electrode additive to the positive electrode active material satisfies 0<r≤0.15.

[0020] A third aspect of the present invention provides a lithium-ion battery, comprising the lithium-ion battery positive electrode sheet provided by the second aspect of the present invention.

[0021] The technical solution of the present invention has the following beneficial effects:

[0022] (1) The positive electrode additive of the lithium ion battery of the present invention can decompose to produce active lithium and gas, thereby replenishing lithium. Charging the battery within a suitable charge and discharge setting range can make the positive electrode additive material Li x A y C2O4 decomposes, and the decomposition product is active lithium Li + and gaseous carbon dioxide CO2. + Used to replenish the active lithium consumed by SEI and increase battery capacity.

[0023] (2) The lithium ion battery positive electrode additive of the present invention has a low lithium desorption potential and a high lithium desorption specific capacity. x A y Due to the introduction of doping atom A in the C2O4 structure, the close adsorption of A and anions weakens the interaction between Li and anions, making it easier for Li to be released during charging, and having a low de-lithiation potential. x A y C2O4 material is used as a positive electrode additive to achieve decomposition and lithium removal under low voltage conditions. This additive is suitable for positive electrode material systems such as LiFePO4, LiMn2O4, and NCM. It can be decomposed at a low voltage of 4.1-4.6V to complete the lithium replenishment of the negative electrode, avoiding the irreversible structural changes of the positive electrode active material under continuous high charging voltage conditions, thereby improving the stability and cycle performance of the battery.

[0024] Other features and advantages of the technical solution of the present invention will be described in detail in the specific implementation section. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 It is the first charge and discharge curve of battery samples S3-S5 and DS1 at a charge and discharge rate of 0.1C;

[0026] Figure 2 It is the first charge and discharge curve of battery samples S4, S6 and S7 at a charge and discharge rate of 0.1C;

[0027] Figure 3This is the first charge and discharge curve of battery samples S4, S8 and S9 at a charge and discharge rate of 0.1C. DETAILED DESCRIPTION

[0028] The first aspect of the present invention provides a positive electrode additive for a lithium ion battery. The positive electrode additive for a lithium ion battery is Li x A y C2O4, in which A is a positively charged ion, and its valence b≥+2.

[0029] Li x A y The cation Li in C2O4 is +1, and the valence b of the high valence state A is ≥ 2. The high valence state makes A and the anion C2O4 2- It has a tight adsorption effect. Tight adsorption has two effects: first, the A ion tightly adsorbs the anion, which weakens the adsorption of the lithium ion and the anion, making it easier to escape, making Li x A y C2O4 has a lower delithiation potential; secondly, A tightly adsorbs anions, which makes it difficult for A itself to escape, thus preventing A ions from escaping to the negative electrode and avoiding the occurrence of side reactions. x A y C2O4 can have a lower lithium desorption potential, which can be reduced to below 4.6V, and active lithium can be extracted at a low potential. The active lithium extracted by the additive is used to supplement the lithium consumption of the negative electrode SEI film, thereby achieving the purpose of supplying lithium to the negative electrode. x A y The low delithiation potential of C2O4 can avoid irreversible destruction of the electrode material structure under high voltage, thereby improving the electrochemical properties of the battery, such as capacity and stability.

[0030] Li x A y In C2O4, the role of A is to weaken Li x A y The interaction between Li and anions in C2O4 reduces the delithiation potential of the material and does not participate in providing active lithium ions to the negative electrode. When the proportion of Li is x, that is, the proportion of doped A ions is y, Li x A y The delithiation potential of C2O4 material decreases, which means that Li x A y When C2O4 is used as a cathode additive, it can decompose and release active lithium at a lower voltage, which is more compatible with the charging cut-off voltage of conventional batteries. x A y In C2O4, the increase in the A ion content means a decrease in the lithium ion content, which will lead to the x A yThe available active lithium content of C2O4 is reduced, and the lithium supplement capacity is low. Therefore, the proportion x of Li should not be too low. A is used as an additive material Li x A y The proportion of A in C2O4 doping ions should not be too high; when x = 2, Li x A y C2O4 material does not contain A, and the proportion of Li is high at this time, with a theoretical mass specific capacity of 526 mAh / g. However, the tight adsorption of high-valent cation A on anions leads to a high delithiation potential of the material, which is poorly compatible with the charging cut-off voltage of conventional batteries. Therefore, the proportion of Li x should not be too high. Therefore, 1<x<2 is limited.

[0031] Taking into account the lithium removal potential and lithium replenishment capacity of the additive material, the value range of x is preferably 1.9≤x<2. Within this range, the binding effect of A ions on anions is sufficient to ensure the preferential release of Li ions, making the additive material Li x A y The delithiation potential of C2O4 is no higher than 4.6V, which will not affect the positive electrode active material, electrolyte and other battery components, while ensuring that Li x A y C2O4 material has a higher specific capacity for lithium replenishment and can provide more active lithium to make up for the active lithium consumed by the negative electrode SEI, without affecting its lithium replenishment effect as a positive electrode additive.

[0032] The selection of different A ions makes the doped A ions have different adsorption effects on anions. The stronger the adsorption of A ions on anions, the weaker the adsorption between Li ions and anions, corresponding to a lower delithiation potential. The higher the valence state of A ions and the smaller the ionic radius, the stronger the adsorption between A ions and anions. The selection of A ions includes but is not limited to the following categories, for example, divalent cations: Mg 2+ , Ca 2+ , Fe 2+ etc.; trivalent cation: Al 3+ , Fe 3+ Cr 3+ etc.; Tetravalent cation: Ti 4+ , Si 4+ ,Ge 4+ wait.

[0033] Li x A yIn C2O4, according to the principle of electrical neutrality, when A is an ion, the valence state of A b0 and x, y satisfy x+b0*y=2. When A is a divalent ion, the atomic proportion y of A is (2-x) / 2; when A is a trivalent ion, the atomic proportion y of A is (2-x) / 3; when A is a tetravalent ion, the atomic proportion y of A is (2-x) / 4; and so on for other high-valent cations. The proportion y of A atoms is determined by its own ionic valence state and the proportion x of Li ions. When A includes more than two ions, Li x A y C2O4 can be specifically written as Li x A 1 y1 A 2 y2 ...A n yn C2O4, of which A 1 , A 2 , A n y The valence state is b1, b2...b n , satisfying x+b1*y1+b2*y2+……+b n *y n =2.

[0034] Li x A y As an additive material that can provide active lithium ions, C2O4 has a strong adsorption effect on anions, which weakens the binding effect of anions on Li, which is beneficial to Li x A y In addition to the decomposition of C2O4 due to the additive material Li x A y The conductivity of C2O4 itself is poor, and good conductivity must be ensured during the charging process, so it needs to be in full contact with the conductive agent to improve its conductivity. x A y When the particle size of C2O4 is too large, the Li x A y C2O4 accounts for Li x A y A low proportion of total C2O4 will result in Li x A y C2O4 decomposes slowly, which easily leads to an increase in the delithiation potential. Polarization to the cut-off voltage makes its decomposition incomplete. x A y The active lithium in C2O4 cannot be fully released to allow Li x A y C2O4 plays the greatest role in replenishing lithium. x A yWhen the particle size of C2O4 is small, it is beneficial for Li x A y C2O4 decomposes, but will lead to Li x A y The secondary agglomeration of C2O4 particles makes the preparation process difficult and will also lead to Li x A y The stability of C2O4 in the air becomes worse and it is easier to absorb water. x A y C2O4 material decomposition lithium supplement performance and physical and chemical properties, Li x A y The average particle size of C2O4 is preferably 50 nm to 10 μm, more preferably 100 nm to 1 μm.

[0035] The above Li x A y The delithiation potential of C2O4 is not higher than 4.6V; preferably, the above Li x A y The delithiation potential of C2O4 is 4.1V to 4.6V. This delithiation potential can be achieved by ensuring that Li x A y C2O4 has a higher specific capacity for lithium replenishment, providing more active lithium to make up for the active lithium consumed by the negative electrode SEI, while not affecting the positive electrode active material, electrolyte and other battery components.

[0036] A second aspect of the present invention provides a lithium ion battery positive electrode plate, comprising the lithium ion battery positive electrode additive provided by the first aspect of the present invention.

[0037] In the present invention, the positive electrode plate of the lithium-ion battery comprises a positive electrode current collector and a positive electrode material layer arranged on the positive electrode current collector; x A y As an additive material, C2O4 is introduced into the positive electrode material layer in a manner including but not limited to direct mixing and coating. x A y C2O4 is directly mixed with positive electrode active materials, conductive agents, binders, etc., and slurry coating is performed to obtain a Li x A y C2O4 positive electrode material layer, at this time, the positive electrode material layer contains a mixed lithium ion battery positive electrode additive, positive electrode active material, conductive agent and binder; coating method, that is, Li x A yC2O4 is mixed with a conductive agent and a binder, and slurried and coated on a positive electrode active material layer comprising a positive electrode active material, a conductive agent and a binder to obtain a multilayer positive electrode material layer containing a positive electrode additive material layer. At this time, the positive electrode material layer comprises a positive electrode active material layer and a positive electrode additive material layer arranged on the positive electrode active material layer, the positive electrode active material layer comprises a positive electrode active material, a conductive agent and a binder, and the positive electrode additive material layer comprises a lithium ion battery positive electrode additive, a conductive agent and a binder; in some embodiments of the present invention, the above-mentioned positive electrode additive material layer may also include a positive electrode active material, that is, the positive electrode additive material layer comprises a lithium ion battery positive electrode additive, a positive electrode active material, a conductive agent and a binder.

[0038] When Li x A y When C2O4 is used as a positive electrode additive material to replenish lithium to the negative electrode, the Li2O4 can be set according to the maximum charge cut-off voltage that the battery system can withstand, taking into account the lithium removal potential and lithium removal specific capacity. x A y The doping amount of high-valent cation A in C2O4 and Li x A y The amount of C2O4 added is to obtain the maximum amount of additive lithium supplement capacity without affecting the battery system. For example, the positive electrode of a lithium-ion battery includes a positive electrode active material, and the types of positive electrode active materials include but are not limited to LiFePO4, LiMn2O4 and NCM ternary materials. Specifically, the chemical formula of NCM ternary material is LiNi a Co c Mn 1-a-c O2, where 0<a<1, 0<c<1.

[0039] The irreversible capacity loss in the reference battery system accounts for 0-20%. To compensate for this part of the lost capacity, the delithiation capacity contributed by the positive electrode additive should be approximately equal to the loss value. Taking into account the delithiation specific capacity of the positive electrode additive and the specific capacity of the positive electrode active material, in the lithium-ion battery positive electrode sheet, the mass ratio r of the lithium-ion battery positive electrode additive to the positive electrode active material satisfies 0<r≤0.15.

[0040] Among them, binders and conductive agents are conventional choices in the field of batteries. For example, the binder can be selected from one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinyl alcohol (PVA), styrene-butadiene rubber (SBR), polyacrylonitrile (PAN), polyimide (PI), polyacrylic acid (PAA), polyacrylate, polyolefin (such as polyethylene, polypropylene, polystyrene), sodium carboxymethyl cellulose (CMC), sodium alginate, etc. The conductive agent can be at least one of carbon black (such as acetylene black, Ketjen black), carbon nanotubes (CNT), graphene, carbon fiber, graphite, etc., but is not limited thereto. In addition, the positive current collector may include but is not limited to metal film materials, foam metal meshes, etc., specifically aluminum foil, carbon-coated aluminum foil, etc. This application has no restrictions on the surface density and compaction of the above-mentioned positive electrode sheet, and can be designed according to the specific electrochemical system.

[0041] In a third aspect, the present invention provides a lithium-ion battery, comprising the lithium-ion battery positive electrode sheet provided in the second aspect of the present invention.

[0042] In addition to the lithium-ion battery positive electrode sheet provided by the second aspect of the present invention, the lithium-ion battery disclosed in the present invention may also include a negative electrode sheet, a separator and an electrolyte.

[0043] In the present application, the negative electrode plate is a conventional choice in the field of batteries. The diaphragm is used to separate the positive electrode plate and the negative electrode plate to maintain the insulation between the two; the diaphragm, the positive electrode plate and the negative electrode plate together constitute the battery cell, and the battery cell is accommodated in the battery shell, and the battery shell can be an aluminum-plastic film. The diaphragm can be a polymer diaphragm, a non-woven fabric and other commonly used battery diaphragms, including but not limited to single-layer PP (polypropylene) film, single-layer PE (polyethylene) film, double-layer PP / PE, double-layer PP / PP and three-layer PP / PE / PP. The battery shell is injected with an electrolyte, which is a medium for the transmission of lithium ions between the positive and negative electrode plates. The specific composition of the electrolyte is a conventional choice in the field of batteries and is not limited to this.

[0044] The preparation method of the above-mentioned lithium-ion battery includes: stacking the positive electrode plate, the separator and the negative electrode plate in sequence to form a battery cell, accommodating the battery cell in a battery shell, injecting an electrolyte, and then sealing the battery shell to obtain a lithium-ion battery.

[0045] The present invention will be further described in detail below through embodiments in conjunction with the accompanying drawings.

[0046] Example 1

[0047] The average particle size of Li is 300 nm. 1.05 Mg 0.475C2O4 is the positive electrode material, acetylene black is the conductive agent, polyvinylidene fluoride (PVDF) is the binder, and N-methylpyrrolidone (NMP) is the dispersant. After being mixed evenly in a mass ratio of positive electrode material: acetylene black: PVDF: NMP = 85:10:5:50, aluminum foil is used as the positive electrode collector for coating, and then placed in a 120℃ oven for vacuum drying for 24 hours, and then pressed and cut into positive electrode sheets. Metal lithium sheets are used as negative electrode sheets, celgard2400 polypropylene porous membranes are used as separators, and a mixed solution of 1mol / LLiPF6 ethylene carbonate (EC) and dimethyl carbonate (DMC) (the volume ratio of EC to DMC is = 1:1) is used as the electrolyte; the test battery is assembled in a glove box filled with argon to obtain battery sample S1.

[0048] Example 2

[0049] The battery sample S2 was prepared by referring to the method in Example 1, except that the positive electrode material used was Li with an average particle size of 300 nm. 1.5 Mg 0.25 C2O4.

[0050] Example 3

[0051] The battery sample S3 was prepared by referring to the method in Example 1, except that the positive electrode material used was Li with an average particle size of 300 nm. 1.9 Mg 0.05 C2O4.

[0052] Example 4

[0053] The battery sample S4 was prepared by referring to the method in Example 1, except that the positive electrode material used was Li with an average particle size of 300 nm. 1.94 Mg 0.03 C2O4.

[0054] Example 5

[0055] The battery sample S5 was prepared by referring to the method in Example 1, except that the positive electrode material used was Li with an average particle size of 300 nm. 1.98 Mg 0.01 C2O4.

[0056] Example 6

[0057] The battery sample S6 was prepared by referring to the method in Example 1, except that the positive electrode material used was Li with an average particle size of 300 nm. 1.94 Ca 0.03 C2O4.

[0058] Example 7

[0059] The battery sample S7 was prepared by referring to the method in Example 1, except that the positive electrode material used was Li with an average particle size of 300 nm. 1.94 Fe 0.03 C2O4.

[0060] Example 8

[0061] The battery sample S8 was prepared by referring to the method in Example 1, except that the positive electrode material used was Li with an average particle size of 300 nm. 1.94 Al 0.02 C2O4.

[0062] Example 9

[0063] The battery sample S9 was prepared by referring to the method in Example 1, except that the positive electrode material used was Li with an average particle size of 300 nm. 1.94 Ti 0.015 C2O4.

[0064] Example 10

[0065] The battery sample S10 was prepared by referring to the method in Example 1, except that the positive electrode material used was Li with an average particle size of 300 nm. 1.94 Mg 0.015 Ca 0.015 C2O4.

[0066] Embodiment 11

[0067] The battery sample S11 was prepared by referring to the method in Example 1, except that the positive electrode material used was Li with an average particle size of 300 nm. 1.94 Mg 0.01 C a0.01 Fe 0.01 C2O4.

[0068] Example 12

[0069] The battery sample S12 was prepared by referring to the method in Example 1, except that the positive electrode material used was Li with an average particle size of 1 μm. 1.94 Mg 0.03 C2O4.

[0070] Example 13

[0071] The positive electrode sheet was prepared by referring to the method in Example 1, except that the positive electrode material used was a positive electrode active material LiFePO4 and a positive electrode additive material Li in a mass ratio of 90:10. 1.05 Mg 0.475C2O4 (the average particle size of the positive electrode additive material is 300nm). Graphite is used as the negative electrode material, styrene-butadiene rubber (SBR) is used as the binder, sodium carboxymethyl cellulose (CMC) is used as the thickener, and water (H2O) is used as the dispersant. After being mixed evenly in a mass ratio of graphite: SBR: CMC: H2O = 100: 3: 2: 50, it is coated on the copper foil, and then placed in a 90°C oven to dry for 24 hours, and then pressed and cut into negative electrode sheets. Celgard2400 polypropylene porous membrane is used as the diaphragm, and a mixed solution of 1 mol / L LiPF6 ethylene carbonate (EC) and dimethyl carbonate (DMC) (volume ratio = 1: 1) is used as the electrolyte; the test battery is assembled in a glove box filled with argon to obtain the battery sample S13.

[0072] Embodiment 14

[0073] The battery sample S14 was prepared by referring to the method in Example 13, except that the positive electrode materials used were LiFePO4 with a mass ratio of 90:10 and Li with an average particle size of 300 nm. 1.5 Mg 0.25 C2O4.

[0074] Embodiment 15

[0075] The battery sample S15 was prepared by referring to the method in Example 13, except that the positive electrode materials used were LiFePO4 with a mass ratio of 90:10 and LiFePO4 with an average particle size of 300 nm. 1.94 Mg 0.03 C2O4.

[0076] Example 16

[0077] The battery sample S16 was prepared by referring to the method in Example 13, except that the positive electrode materials used were LiFePO4 with a mass ratio of 90:10 and Li with an average particle size of 300 nm. 1.94 Ca 0.03 C2O4.

[0078] Embodiment 17

[0079] The battery sample S17 was prepared by referring to the method in Example 13, except that the positive electrode materials used were LiFePO4 with a mass ratio of 90:10 and LiFePO4 with an average particle size of 300 nm. 1.94 Mg 0.015 Ca 0.015 C2O4.

[0080] Embodiment 18

[0081] (1) LiFePO4 was used as a positive electrode active material, acetylene black was used as a conductive agent, polyvinylidene fluoride (PVDF) was used as a binder, and N-methylpyrrolidone (NMP) was used as a dispersant. The mixture was uniformly mixed in a mass ratio of positive electrode active material: acetylene black: PVDF: NMP = 85:10:5:50, and then coated with aluminum foil as a positive electrode current collector. The mixture was then placed in an oven at 120°C and vacuum dried for 24 hours to obtain a positive electrode active material layer.

[0082] (2) According to the mass ratio, the positive electrode additive material Li 1.94 Mg 0.03 C2O4: acetylene black: PVDF: NMP = 85: 10: 5: 50 are mixed evenly to obtain a mixed slurry, which is then coated on the positive electrode active material layer obtained in step (1), and then placed in a 120°C oven for vacuum drying for 24 hours, and then pressed and cut into sheets to form a composite positive electrode sheet. In the positive electrode sheet, LiFePO4 and Li 1.94 Mg 0.03 The mass ratio of C2O4 is 90:10.

[0083] (3) Graphite is used as the negative electrode material, styrene-butadiene rubber (SBR) is used as the binder, sodium carboxymethyl cellulose (CMC) is used as the thickener, and water (H2O) is used as the dispersant. The mixture is uniformly mixed in a mass ratio of graphite: SBR: CMC: H2O = 100: 3: 2: 50, and then coated on a copper foil, and then placed in a 90°C oven for drying for 24 hours, and then pressed and cut into pieces to form a negative electrode sheet. The composite positive electrode sheet prepared in step (2) is used as the positive electrode sheet, Celgard 2400 polypropylene porous membrane is used as the diaphragm, and a mixed solution of 1 mol / L LiPF6 ethylene carbonate (EC) and dimethyl carbonate (DMC) (volume ratio = 1: 1) is used as the electrolyte; the test battery is assembled in a glove box filled with argon to obtain a battery sample S18.

[0084] Comparative Example 1

[0085] The battery sample DS1 was manufactured by referring to the method in Example 1, except that the positive electrode material used was Li2C2O4.

[0086] Comparative Example 2

[0087] The battery sample DS2 was manufactured by referring to the method in Example 8, except that the positive electrode material used was LiFePO4.

[0088] Elemental quantitative analysis

[0089] According to EPA6010D-2018D inductively coupled plasma atomic emission spectrometry, ICP-OES-inductively coupled plasma emission spectrometer was used to analyze the positive electrode additive Li x Ay C2O4 element quantitative analysis. In the element quantitative analysis test results in Table 1,

[0090] Li x A y , in C2O4:

[0091] Li mass percentage = total mass of Li / total mass of (Li+A);

[0092] A mass percentage = A total mass / (Li + A) total mass;

[0093] The conversion calculation can obtain x and y respectively.

[0094] Table 1 shows the 12 different positive electrode materials Li in Examples 1-12. x A y Quantitative element analysis of C2O4. According to the mass ratio of Li and A, the corresponding molar ratio can be calculated to calculate Li x A y The x and y values ​​in C2O4.

[0095] Table 1

[0096]

[0097] Li x A y C2O4 material decomposition performance test

[0098] First lithium removal specific capacity (mAh / g) = first lithium removal capacity / mass of active material

[0099] Theoretical first lithium removal capacity (mAh / g) = theoretical total Li removal capacity / mass of active material

[0100] Among them, the first lithium removal specific capacity measured by S1-S12 reflects the Li x A y The delithiation specific capacity of C2O4 material. The test method of the first delithiation specific capacity is: in the blue battery test cabinet, the battery sample is charged at a charging current density of 0.1C to a cut-off voltage of 4.6V or 4.8V, and then the operation is stopped to obtain the first delithiation specific capacity.

[0101] The calculation method of the theoretical first lithium removal specific capacity (corresponding to the theoretical total Li removal capacity) is as follows:

[0102] (1) 1 mol of Li x A y C2O4 material can remove x mol of lithium;

[0103] (2) The charge of x mol of Li = x mol*6.02*10 23 mol -1 *1.602*10 -19 C=x mol*6.02*10 23 mol -1 *1.602*10 -19 A·S=x mol*6.02*10 23 mol -1 *1.602*10 -19 *(1000 / 3600)mAh, get the power in mAh;

[0104] (3) The power in mAh calculated in step (2) is divided by Li x A y The mass of C2O4 in g is used to obtain the theoretical first delithiation specific capacity, and the unit of the theoretical first delithiation specific capacity is mAh / g.

[0105] The test method for the first charging voltage platform is: using constant current charging in a blue battery test cabinet, charging the battery sample at a charging current density of 0.1C to a cut-off voltage of 4.6V or 4.8V and then stopping the operation to obtain a charging voltage-specific capacity curve (first charge and discharge curve). The platform of the charging voltage-specific capacity curve corresponds to the first charging voltage platform of the battery.

[0106] Examples 1-12 are all based on Li x A y C2O4 material is used as the positive electrode active material of the battery in order to test Li x A y The delithiation potential of C2O4 material (i.e., the first charging voltage platform measured by the battery samples S1-S12 of Examples 1-12) and the first delithiation specific capacity (i.e., the first delithiation specific capacity measured by the battery samples of Examples 1-12) are as follows: x A y The verification of C2O4 as a battery positive electrode additive is in the next part of the lithium replenishment performance test.

[0107] In Examples 1-12, the main material of the positive electrode of the battery is Li x A y C2O4, during the first charge, Li x A y C2O4 begins to decompose and release active lithium at a certain voltage platform. x A yThe decomposition performance of C2O4 includes two aspects: one is the initial lithium removal capacity, and the other is the lithium removal potential. The initial lithium removal capacity of battery samples S1-S12 of Examples 1-12 reflects the Li x A y The active lithium capacity released by C2O4 after delithiation; the delithiation potential corresponds to Li x A y The potential required for C2O4 to decompose and release active lithium reacts with Li x A y The ease of decomposition of C2O4 and the delithiation potential are reflected by the first charging voltage platform of battery samples S1-S12 in Examples 1-12. When the delithiation potential is reached, Li x A y C2O4 decomposes and releases lithium ions. The lower the lithium removal potential, the higher the lithium removal capacity. x A y The lithium replenishment performance is better when C2O4 is used as a positive electrode additive.

[0108] (1) Li with the same cation A, the same valence, and different Li ratios x A y Comparison of C2O4 decomposition performance

[0109] Figure 1 The first charge and discharge curves of battery samples S3-S5 and DS1 at a charge and discharge rate of 0.1 C. The test results of the first delithiation specific capacity and the first charging voltage platform of battery samples S1-S5 and DS1 are shown in Table 2. It can be found that the theoretical first lithium desorption capacity increases with the increase of Li content, and the theoretical value becomes higher. This is because the partially substituted A does not participate in the decomposition and release, and will not contribute to the capacity. Comparing the theoretical and actual lithium desorption capacity, S1-S5 are all completely delithiated at 4.6V, releasing the theoretical amount of active lithium, while DS1 is Li2C2O4 that is not doped with high-valent cations. The actual lithium desorption capacity is only 64.6% of the theoretical value at a cut-off voltage of 4.8V, and Li is not completely desorbed. Comparing the charging voltage platform, that is, the Li desorption platform potential (lithium desorption potential), the higher the Li content, the less high-valent cation A is doped, and the higher the lithium desorption potential. The lithium desorption potential of each battery sample is DS1-4.7V>S5-4.58V>S5-4.49V>S3-4.43V>S2-4.29V>S1-4.18V. Therefore, Li x A y After part of the Li in the C2O4 material is replaced by A, its delithiation potential is reduced and the actual available active lithium capacity is improved.

[0110] Table 2

[0111]

[0112] The test results show that the first charging voltage platform of the DS1 sample is at 4.7V. When the charging cut-off potential is set at 4.6V, the DS1 sample does not decompose, and the first lithium removal capacity is about zero. In the battery system with a cut-off potential of 4.6V, the S1-S5 samples have higher actual first lithium removal capacity than the DS1 sample, indicating that the Li x A y C2O4 can provide more active lithium to the negative electrode than Li2C2O4. At the same time, S1-S5 has a lower first charge voltage platform than DS1, indicating that Li x A y When C2O4 is used as a positive electrode additive material, it can decompose and release active lithium under lower voltage conditions, which can avoid the influence of high charging voltage on the structure of positive electrode active materials and improve the stability and cycle performance of the battery.

[0113] (2) Li with the same valence, the same Li ratio, and different cation A x A y Comparison of decomposition performance of C2O4 materials

[0114] Figure 2 It is the first charge and discharge curve of battery samples S4, S6 and S7 at a charge and discharge rate of 0.1C. The test results of the first delithiation specific capacity and the first charging voltage platform are shown in Table 3. It can be found that when the Li ratio is consistent and only the relative atomic mass of a small amount of doped high-valent ions Mg, Ca and Fe is different, the theoretical first delithiation specific capacity has a small difference and is basically consistent. Comparing the theoretical and actual first delithiation specific capacities, S4, S6 and S7 are all completely delithiated at 4.6V, releasing the theoretical amount of active lithium. When the A ion valence state is consistent and the Li ratio is consistent, the first charging voltage platform, that is, the Li delithiation platform potential (delithiation potential), is S6-4.54V>S7-4.51V>S4-4.49V, which leads to the difference in delithiation potential mainly related to the ionic radius of the doped high-valent cations, and the ionic radii are respectively The smaller the ion radius, the stronger the anion adsorption, which makes the interaction between Li and anions weaker, making it easier to release during charging and the de-lithiation potential lower. x A y After part of the Li in the C2O4 material is replaced by A, its delithiation potential is reduced and the actual available active lithium capacity is improved.

[0115] Table 3

[0116]

[0117]

[0118] (3) Li with the same Li ratio, different valence states, and different cation Ax A y Comparison of decomposition performance of C2O4 materials

[0119] Figure 3 This is the first charge and discharge curve of battery samples S4, S8 and S9 at a charge and discharge rate of 0.1C. The test results of the first delithiation capacity and the first charging voltage platform are shown in Table 4. It can be found that the theoretical first delithiation capacity has a small difference and is basically consistent when the Li ratio is consistent and only the relative atomic mass of a small amount of high-valent ions Mg, Al and Ti are doped; comparing the theoretical and actual first delithiation capacity, S4, S8 and S9 are all completely delithiated at 4.6V, releasing the theoretical amount of active lithium; comparing the charging voltage platform, that is, the Li desorption platform potential (delithiation potential), when the Li ratio is consistent, it shows S4-4.49V>S8-4.44V>S9-4.39V. The difference between this group and (2) group S4, S6 and S7 is that the valence state of A ions in this group is also different, so the difference in delithiation potential is related to the valence state and ionic radius of A ions. The valence state and ionic radius of A ions are respectively The higher the ion valence, the smaller the radius and the stronger the anion adsorption, the weaker the interaction between Li and anions, the easier it is to escape during charging, and the lower the delithiation potential. The first charge voltage platform data is S4>S8>S9. Comparing the first charge voltage platform data of S8 and S9, it can be seen that the influence of the A ion valence on the first charge voltage platform is greater than the ion radius. Compared with DS1, the delithiation potentials of S4, S8 and S9 are all significantly reduced, and the actual available active lithium capacity is increased.

[0120] Table 4

[0121]

[0122] (4) Li co-doped with cation A x A y C2O4 material decomposition performance

[0123] The test results of the first delithiation capacity and the first charging voltage platform of different cation co-doping are shown in Table 5. Comparing the theoretical and actual first delithiation capacity, S10 and S11 are completely delithiated at 4.6V, releasing the theoretical amount of active lithium. Compared with DS1, the first delithiation capacity of S10 and S11 is significantly improved, and the decomposition potential is reduced. Therefore, Li x A y After part of the Li in the C2O4 material is replaced by multiple A atoms, its delithiation potential is reduced and the actual available active lithium capacity is improved.

[0124] Table 5

[0125]

[0126] (5) Li with different particle sizes 1.94 Mg 0.03 Comparison of decomposition performance of C2O4 materials

[0127] Li particles of different sizes 1.94 Mg 0.03 The decomposition performance of C2O4 materials (first lithium removal capacity and first charging voltage platform) is shown in Table 6. Comparing the theoretical and actual lithium removal capacity, S4 and S12 are completely lithium-free at 4.6V, releasing the theoretical amount of active lithium; comparing the first charging voltage platform, i.e., the lithium removal potential, it shows that S12-4.58V>S4-4.49V, resulting in the difference in lithium removal potential mainly due to Li 1.94 Mg 0.03 It is related to the particle size of C2O4 material. S4 uses particles with a low average particle size of 300nm, while S12 uses large particles with an average particle size of 1μm. The smaller the particle size, the better the electrical contact with the conductive agent, electrolyte, etc., the smaller the battery polarization will be, and the corresponding delithiation potential will be lower. The larger the particle size, the greater the battery polarization will be, resulting in a higher delithiation potential.

[0128] Table 6

[0129]

[0130] Li x A y Lithium replenishment performance test of C2O4 material

[0131] Examples 13-18 are Li x A y C2O4 material is introduced into the LFP battery system as a positive electrode additive material, and the quality of the positive electrode materials described in S13-S17 and DS2 is the same, and the LiFePO4 and Li in S18 are 1.94 Mg 0.03 The total mass of C2O4 is the same as the mass of the positive electrode material described in S13-S17. x A y The lithium replenishment effect of C2O4 material, the active lithium released by its decomposition can be used to make up for the active lithium consumed by the negative electrode SEI, thereby increasing the battery capacity.

[0132] The test method for the first charging capacity is: using constant current charging and discharging in the blue power battery test cabinet, charge the battery sample at a charging current density of 0.1C to a cut-off voltage of 4.6V and stop charging, and then charge at a wind power current density of 0.1C to a cut-off voltage of 2V and stop running.

[0133] The test method for the first discharge capacity is: using a constant current charge and discharge method in a blue power battery test cabinet, charging the battery sample at a charging current density of 0.1C to a cut-off voltage of 4.6V and then stopping charging, and then charging at a wind power current density of 0.1C to a cut-off voltage of 2V and then stopping operation. The charge and discharge regime of batteries S13-S18 and DS2 is a charging cut-off voltage of 4.6V and a discharge cut-off voltage of 2.00V. The first charge and discharge capacities of batteries S13-18 and DS2 are listed in Table 7. The results show that the positive electrode active material LiFePO4 of the DS2 battery has a capacity of 1082.1mAh for the first charge, and the negative electrode SEI generation consumes about 12% of the active lithium, so that only 952.2mAh can be embedded back in the first discharge; while the positive electrode plates of S13-S18 introduce the additive Li x A y C2O4 decomposes to provide active lithium during the charging process. The battery discharge capacity is basically the same as the charging capacity of DS2, indicating that Li x A y The active lithium provided by the decomposition of C2O4 during the charging process can meet the consumption of SEI film, replenish sufficient active lithium, and enable sufficient active lithium to be discharged and embedded back into LiFePO4. x A y C2O4 material can replenish the active lithium consumed by the negative electrode SEI film, thereby significantly improving the capacity of the battery.

[0134] Table 7

[0135] Battery ID First charge capacity mAh First discharge capacity mAh S13 1170.8 1069.7 S14 1231.3 1070.5 S15 1293.2 1079.3 S16 1299.6 1078.4 S17 1308.5 1073.6 S18 1293.7 1071.3 DS2 1082.1 952.2

Claims

1. A positive electrode additive for lithium ion batteries, characterized in that: The positive electrode additive of the lithium ion battery is Li x A y C2O4, the valence of A is ≥+2, 1<x<2; The Li x A y In C2O4, A is selected from at least one of a divalent cation, a trivalent cation and a tetravalent cation; When A is a divalent cation, A selects Mg 2+ , Ca 2+ At least one of; The Li x A y The average particle size of C2O4 is 100nm~1μm.

2. The lithium ion battery positive electrode additive according to claim 1, characterized in that: The Li x A y In C2O4, 1.5≤x<2.

3. The lithium ion battery positive electrode additive according to claim 1, characterized in that The Li x A y In C2O4, 1.9≤x<2.

4. The lithium ion battery positive electrode additive according to claim 1, characterized in that: The Li x A y In C2O4, A also selects Al 3+ , Fe 3+ Cr 3+ 、Ti 4+ , Si 4+ and Ge 4+ At least one of .

5. The lithium ion battery positive electrode additive according to claim 1, characterized in that: The Li x A y The delithiation potential of C2O4 is no higher than 4.6V.

6. The lithium ion battery positive electrode additive according to claim 1, characterized in that: The Li x A y The delithiation potential of C2O4 is 4.1V~4.6V.

7. A positive electrode plate for a lithium-ion battery, characterized in that: The lithium-ion battery positive electrode plate comprises the lithium-ion battery positive electrode additive according to any one of claims 1 to 6.

8. The positive electrode plate of a lithium-ion battery according to claim 7, characterized in that: The positive electrode plate of the lithium-ion battery comprises a positive electrode current collector and a positive electrode material layer disposed on the positive electrode current collector; the positive electrode material layer satisfies the following conditions (1) or (2): (1) The positive electrode material layer comprises the lithium ion battery positive electrode additive and the positive electrode active material; (2) The positive electrode material layer includes a positive electrode active material layer and a positive electrode additive material layer disposed on the positive electrode active material layer, the positive electrode active material layer includes a positive electrode active material, and the positive electrode additive material layer includes the lithium ion battery positive electrode additive.

9. The positive electrode sheet of a lithium-ion battery according to claim 7 or 8, characterized in that: The lithium-ion battery positive electrode plate includes a positive electrode active material, and the positive electrode active material is selected from at least one of LiFePO4, LiMn2O4 and nickel-cobalt-manganese ternary materials; in the lithium-ion battery positive electrode plate, the mass ratio r of the lithium-ion battery positive electrode additive to the positive electrode active material satisfies 0<r≤0.

15.

10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the lithium-ion battery positive electrode sheet according to any one of claims 7 to 9.

Citation Information

Patent Citations

  • Preparation method of KLi3Fe(C2O4)3, battery positive electrode active material, battery and electric equipment

    CN111349000A